2017
DOI: 10.1038/s41598-017-08715-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic compounds identified in Piriformospora indica-colonized Chinese cabbage roots delineate symbiotic functions of the interaction

Abstract: Root colonization by endophytic fungus Piriformospora indica facilitating growth/development and stress tolerance has been demonstrated in various host plants. However, global metabolomic studies are rare. By using high-throughput gas-chromatography-based mass spectrometry, 549 metabolites of 1,126 total compounds observed were identified in colonized and uncolonized Chinese cabbage roots, and hyphae of P. indica. The analyses demonstrate that the host metabolomic compounds and metabolite pathways are globally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…Such a variety of roles at the plant‐microorganisms interface points to the centrality of GABA in interkingdom signalling. In agreement with this notion, GABA was shown to be involved in coordinating metabolic balances in rhizobia‐legume symbiosis (Nasr et al, ; Sulieman & Schulze, ) and symbiosis with mutualistic microbes such as Piriformospora indica (Hua, Kumar, Shyur, & Cheng, ).…”
Section: A Molecular Swiss Knife: Gaba Functions In Relation To Pathomentioning
confidence: 72%
“…Such a variety of roles at the plant‐microorganisms interface points to the centrality of GABA in interkingdom signalling. In agreement with this notion, GABA was shown to be involved in coordinating metabolic balances in rhizobia‐legume symbiosis (Nasr et al, ; Sulieman & Schulze, ) and symbiosis with mutualistic microbes such as Piriformospora indica (Hua, Kumar, Shyur, & Cheng, ).…”
Section: A Molecular Swiss Knife: Gaba Functions In Relation To Pathomentioning
confidence: 72%
“…Indeed, by using diverse approaches, including screening Arabidopsis mutants and/or reporter lines and interfering with hormone biosynthesis or transport ( Zhang et al, 2007 ; Ortíz-Castro et al, 2008 ; Bhattacharyya et al, 2015 ; Bitas et al, 2015 ; Garnica-Vergara et al, 2016 ; Sánchez-López et al, 2016a ; Pérez-Flores et al, 2017 ; Li et al, 2018 ) as well as transcriptomics ( Zhang et al, 2007 ; Bhattacharyya et al, 2015 ; Sánchez-López et al, 2016a ) and proteomics ( Kwon et al, 2010 ; Sánchez-López et al, 2016b ), it was shown that mainly auxin and cytokinin production and signaling as well as auxin transport were affected by microbial VOCs, indicating that plants react to these volatiles through highly conserved regulatory mechanisms. Interestingly, plant growth promotion due to physical contact between S. indica and Arabidopsis also appeared to be linked to auxin signaling ( Schäfer et al, 2009 ; Lee et al, 2011 ; Dong et al, 2013 ; Ye et al, 2014 ; Hua et al, 2017 ) and cytokinin perception (through CRE1/AHK2; Vadassery et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, P. indica mutants with reduced IAA levels due to the silencing of tryptophan aminotransferase ( piTam1 ) showed an average growth‐promoting effect on barley but reduced colonization of roots during the biotrophy stage, suggesting that auxin might act as a signal for communication with host plants (Hilbert et al, ). In addition, an exudate fraction from P. indica , but not auxin, stimulates the growth of Chinese cabbage (Hua et al, ). In the present study, we found that expression of the IAA synthesis gene in F. oryzae was not significantly upregulated at 7 days after cocultivation when F. oryzae had already stimulated root hair growth.…”
Section: Discussionmentioning
confidence: 99%